Research on financial risk management and control of agricultural products supply chain—A case study of Jiangsu Province of China - Yang, Jing; Tang, Decai; Kong, Haojia; Boamah, Valentina (Frontiers in Environmental Science, 2022)
Agriculture has always been the focus of all countries, the rapid development of agriculture is inseparable from the strong support of finance. As a new financial model, agricultural product supply chain finance has attracted much attention. Through the analysis of the agricultural product supply chain finance model, we find that the core problem of agricultural supply chain finance is the management and control of supply chain financial risks. Based on the identification of financial risk categories of agricultural products supply chain, this paper constructs tan evaluation index system. Taking Jiangsu Province of China as the research object, this research collects relevant data of financial institutions, logistics enterprises, agricultural product production, and processing enterprises and farmers in southern and northern Jiangsu Province in 2021. The structural equation is used to establish the model. This statistical method can handle multiple potential variables at the same time, and allows observation variables and potential variables to contain measurement errors. The application of statistical methods that can handle multiple potential variables at the same time and allow observation variables and potential variables to contain measurement errors to build a model. By using the Amos calculation model, this research found that the factors affecting the financial risks of the agricultural product supply chain in Jiangsu Province from high to low are: the agricultural product pledge risks, the credit risks, the supply chain operation risks, the technical risks, the legal and policy risk. We hope this research can play a theoretical guiding role for the effective development of agricultural product supply chain finance business.